A Model; Road Map to Achieve Sustainable Development Goals 2030 Realizing Your Potential a Proposed Guidelines for National Health Policy for Integrated Health Care Delivery - Asif Maqsood Butt, Omaima Asif, (Journal of Rawalpindi Medical College, 2021)
The goals that are set for 2030 regarding sustainable Development are a wakeup call to action that reforms should be made to end poverty, protect the planet and ensure health for all and everywhere. The needs to review and reprioritize the use of existing resources in the health sector along with significant addition and allocation of resources for health should be focusing more on primary health care. Pakistan must also adopt a holistic integrated approach that views health, education, and other social sector development as intrinsically interrelated and interwoven. Most of the patients in Pakistan visit two to three general practitioner / family physicians to rule out and to know the exact diagnosis of their ailment. This increases the frequency of visits to the other physicians and decreases follow up and compliance concerning to the treatment provided. Another Important concern is record maintenance as most of the time patient loss their important notes/ reports. So to streamline these all patient record as well as provision of safe treatment and referral if any needed in the region he is residing are the main purpose; this will decrease patient load to Private as well as public sector health units and will decrease the unnecessary movement of patients. The Unique Model by Using the latest Technology has evolved by putting the Communication, Coordination in a synchronization pattern and by keeping the health care provider and client in a centralized position. This will integrate all levels of family Physicians; centralize the patient registration Mechanism in Pakistan. This will regulate Screenings & Surveillance of Communicable and Non communicable Diseases thus support the District Health Administration to keep an eagle eye to monitor disease prevalence and incidence. This will work in coordination with Primary secondary and specialized healthcare; Tertiary health care units Public Sector. The efficient and effective Decrease the Chronicity, Resistance and Poor Compliance OBJECTIVES: To strengthen the feedback and Reporting System in Pakistan. To Improve Tracking System, Patient’s Health Care, Surveillance, Coordination, Team Facilitation & Integration hence help in policy development METHODOLOGY: This will be a unique Web Portal System with customized features The integrated model will be configured and synchronized; based on integrated, self-regulated concept. It’s all sections shall be interconnected and reports will be auto generated after a concrete analysis and Produce comparative results instantly. RESULTS: Rapid communication and Instant strategies policies to improve patient’s health care, by improving the surveillance & tracking system in Pakistan CONCLUSIONS: The “Integration Model For Pre & Post Epidemic Communication, Strategies will help to Improve Tracking System, Patient’s Health Care, Surveillance, Coordination, Team Facilitation as well as strengthening the feedback and Reporting System In Pakistan”. This will also help the District Health Authority & District Administration for proper and appropriate measures to initiate.